Ebola Virus Disease Outbreaks – A Systematic Review - Yasir Akbar Jamali, Siraj Nabi Depar, Hajira Naila Rahu, Ali Bux Khuhro, Waseem Akram, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The expansion of the Ebola virus has created illnesses that are deadly to both animals and people. This spread has been driven by the rise of urbanization, the invasion of wooded regions, and the intimate connection with wildlife creatures. To this day, the Ebola virus illness, also known as EVD, has been responsible for the deaths of a significant number of people, with the continent of Africa reporting the highest incidence of the disease. Aim: In order to investigate the Ebola outbreaks, as well as morbidity and fatality rates among EVD patients, a systematic review was carried out. Method: Using MeSH keywords like Ebola outbreaks, Ebola virus disease, Ebola disease, and Ebola Epidemic, we searched Google Scholar, Science Direct, and PubMed for articles on EVD epidemics published between 1976 and 2022. Results: Gabon, Guinea, the Republic of the Congo, and Zaire/Democratic Republic of the Congo have all been epicenters for at least 17 EVD epidemics since EBOV was first discovered in 1976. Although case statistics may vary significantly from source to source, as of this writing, there have been an estimated 34,442 EBOV infections in humans, with 4100 (11.9%) fatalities. Conclusion: Multiple EVD pandemics have emerged, mostly in Africa. Although the exact point of genesis of the Ebola virus remains unknown, we do know that direct contact with infected animals may potentially convey the illness to humans. Keywords: Ebola, Ebola Virus Disease, Ebola outbreaks, EVD, Ebola epidemic